CODE-SWITCHING IN WHATSAPP-EXCHANGES: CULTURAL OR LANGUAGE BARRIER? - Idha Nurhamidah (Proceedings Education and Language International Conference, 2017)
This paper explores the employment of code-switching in Social Media ‘Whats-app (WA)’ Bahasa text, namely from Bahasa to Javanese, English and/or to Arabic. Two WA groups are chosen namely ‘Trending Topic’ and ‘LPPM’ WA group as they are more universal chat places for Unissula academia than other faculty limited members of WA groups. This is a descriptive qualitative research, deeply analyzing several purposefully selected data. Interviews with some members of WA groups were performed to gain some data related to the use of code switching. The writer found that the main reason for code-switching is therefore to keep on communication by using technology-related, Koranic-related or Javanese-colloquial terms to try to refer to certain concepts of which the equivalence for such terms are not available in Bahasa. Another reason is to gain closer-relationship among attendants. For this socio-linguistic phenomenon, the writer feels that it is necessary for Bahasa experts or scholars to coin and popularize more Bahasa lexical items required to accommodate the new concepts. Key words: code-switching, Bahasa, Bahasa Experts, technology-related terms, Koranic-related terms, Javanese-colloquialterms